Quantifying the Wollaston Illusion. (May 2020) - Hecht, Heiko; Siebrand, Stefanie; Thönes, Sven
In the early 19th century, William H. Wollaston impressed the Royal Society of London with engravings of portraits. He manipulated facial features, such as the nose, and thereby dramatically changed the perceived gaze direction, although the eye region with iris and eye socket had remained unaltered. This Wollaston illusion has been replicated numerous times but never with the original stimuli. We took the eyes (pupil and iris) from Wollaston's most prominent engraving and measured their perceived gaze direction in an analog fashion. We then systematically added facial features (eye socket, eyebrows, nose, skull, and hair). These features had the power to divert perceived gaze direction by up to 20°, which confirms Wollaston's phenomenal observation. The effect can be thought of as an attractor effect, that is, cues that indicate a slight change in head orientation have the power to divert perceived gaze direction.